GIS-AHP for Optimal Solar Site Selection: A Case Study of Iraq and Its Implications for Climate Change - Nassif, Wedyan Galib; K. Al-Timimi, Yaseen; Elhmaidi, Dalila (International Journal of Sustainable Energy Planning and Management, 2025)
Interest in renewable energy sources to meet the energy needs of tomorrow has sharply increased across the world. This applies particularly to wind power and solar power, forward-oriented industries which have both achieved rapid development in recent years. Large-scale solar photovoltaic (SPV) projects can be easily completed in just 10-15 years, depending on the timeline for government approval. On-site water storage, continuous access to transportation, the ability of the local workforce and availability of solar panels will influence total cost for a given configuration. Taking all of these factors into account helps make sure, that an currently illegal but possible proposal will become illegal in the future too. This study uses GIS (Geographic Information System) and MCDM (Multi-Criteria Decision-Making) to give an initial evaluation of the best locations for large-scale SPV plants in Iraq. The Analytical Hierarchy Process (AHP) was then applied to weight the individual criteria, and integrate them into final suitability mapping with ArcGIS 10.8 software. The results indicate that 27,614 km² (6.3% of Iraq's total area) is suitable for SPV installation, and that annual generation potential varies from 8,700 to 12,595 MWh / km². If 5-20% of these areas are used around the world, then a total of between 3.39 and 13.54 TWh could be provided by SPV installations each year on land. With an efficiency level 15%. As our climate models show average temperatures may reach 34-35°C by the year 2100, this could cause SPV efficiency to fall